The Great Seljuk Empire - Peacock, A. C. S. (Andrew C. S.) (Edinburgh history of the Islamic empires., 2015)
The Great Seljuk Empire was the Turkish state which dominated the Middle East and Central Asia in the eleventh and twelfth centuries. This book surveys that period, which was one of exceptional importance, witnessing profound demographic, religious, political and social changes in the Islamic Middle East. The Turkish invasions played a role in provoking the Crusades, led to the collapse of Byzantine power in Anatolia and brought about the beginnings of Turkish settlement in what is now Turkey and Iran, permanently altering their ethnic and linguistic composition. Key Features The first book in a western language to offer an overview of this major Islamic empire Provides a narrative history and a thematic analysis of the empire's institutions and aspects of life in the Seljuk world Examines the political, administrative, military, religious, economic and social organization of the Great Seljuk Empire using a wide variety of historical and literary sources Draws on the evidence of archaeology and material culture Illustrated with images, maps, charts, family trees Text boxes introduce key themes and institutions